2016
DOI: 10.1016/j.humimm.2015.10.010
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect of HLA-DQB1 alleles against alloimmunization in patients with sickle cell disease

Abstract: Background Alloimmunization or the development of alloantibodies to Red Blood Cell (RBC) antigens is considered one of the major complications after RBC transfusions in patients with sickle cell disease (SCD) and can lead to both acute and delayed hemolytic reactions. It has been suggested that polymorphisms in HLA genes, may play a role in alloimmunization. We conducted a retrospective study analyzing the influence of HLA-DRB1 and DQB1 genetic diversity on RBC-alloimmunization. Study design Two-hundred four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…and -DQB1*05, inferring a protector role of the HLA-DQB1*03 allele for African-American SDC patients (Tatari-Calderone et al, 2016). However, no other study has associated red blood cell alloimmunisation to the HLA-A*23 and HLA-C*06 allelic variants, as we observed in this study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…and -DQB1*05, inferring a protector role of the HLA-DQB1*03 allele for African-American SDC patients (Tatari-Calderone et al, 2016). However, no other study has associated red blood cell alloimmunisation to the HLA-A*23 and HLA-C*06 allelic variants, as we observed in this study.…”
Section: Discussionsupporting
confidence: 50%
“…() studied 159 American polytransfused patients with SCA and observed that HLA‐DRB1*15:03 was associated with the risk of developing alloantibodies ( P = 0·03, OR = 2·02), whereas the HLA‐DRB1*09:01 conferred protection to patients who did not alloimmunise ( P = 0·008, OR = 0·13); however, such an association was not observed in our study. In contrast, another group of researchers found an association between the alloantibody‐negative group and HLA‐DQB1*02 , −DQB1*03 and –DQB1*05 , inferring a protector role of the HLA‐DQB1*03 allele for African‐American SDC patients (Tatari‐Calderone et al, ). However, no other study has associated red blood cell alloimmunisation to the HLA‐A*23 and HLA‐C*06 allelic variants, as we observed in this study.…”
Section: Discussionmentioning
confidence: 94%
“…A new protective factor for Fy a alloimmunization, the DQB1*02 allele, was found in this study. The protective effect of the DQB1*02 was also shown for the alloimmunization of patients with sickle cell disease …”
Section: Discussionmentioning
confidence: 88%
“…Patients with SCD present a steady-state inflammatory status (Pitanga et al, 2016). Although some studies addressed the role of inflammatory proteins and cells in SCD (Styles et al, 2000;Tamouza et al, 2002;Hoppe et al, 2003;Adekile et al, 2005;Wallace et al, 2009;Wallace & Linden, 2010;Vingert et al, 2015;Godefroy et al, 2016;Pitanga et al, 2016;Tatari-Calderone et al, 2016), few studies have investigated the potential associations between SCD complications and polymorphisms in genes encoding inflammatory proteins (Norris et al, 1996;Neonato et al, 1999;Styles et al, 2000;Tamouza et al, 2002;Hoppe et al, 2003;Adekile et al, 2005;Fertrin & Costa, 2010;Tatari-Calderone et al, 2016;Sippert et al, 2017;David et al, 2018). In this context, Toll-like receptors (TLRs) are a family of transmembrane and intra-cellular proteins expressed on immune cells that sense pathogen-associated molecular patterns (PAMPs) and endogenous damage-associated molecular patterns (DAMPs).…”
Section: Discussionmentioning
confidence: 99%